Development of non-rare earth grain boundary modification techniques for Nd-Fe-B permanent magnets. (30th January 2022) - Liu, Zhongwu; He, Jiayi; Zhou, Qing; Huang, Youlin; Jiang, Qingzheng
Highlights: The development of grain boundary modification for Nd-Fe-B magnets is summarized. The cost-effective non-rare earth (non-RE) diffusion sources are emphasized. The properties-microstructure relationships of non-RE modified magnets are discussed. Non-RE modification can enhance both magnetic properties and corrosion resistance of magnets. The opportunity and future directions of are expected. Abstract: The magnetic performance of Nd-Fe-B magnets depends on their grain boundary structure. Intergranular addition and grain boundary diffusion (GBD) process are effective approaches for enhancing coercivity with low material cost. This review summarizes the development of grain boundary modification techniques with emphasis on our recent work using cost-effective non-rare earth (non-RE) sources for GBD. Up to now, heavy rare earth (HRE) based compounds, metals and light rare earth (LRE) based alloys have been successfully employed as the diffusion sources for coercivity enhancement. Inspired from the previous investigations on the intergranular addition of non-RE compounds and alloys for Nd-Fe-B magnets, in 2015, we firstly proposed a novel GBD process based on diffusion source of MgO. After that, various non-RE diffusion sources have been developed. The fundamentals of non-RE additives and non-RE diffusion sources for hard magnetic properties enhancement of Nd-Fe-B magnets are summarized here based on both the experimental and computational results. In particular, the properties-microstructure relationships of non-RE GBD modified magnets are discussed. The non-RE alloys or compounds modify the composition and structure of the grain boundary by diffusing into the intergranular regions, resulting in enhanced coercivity and corrosion resistance. Recently, we used Al-Cr coatings for both coercivity enhancement and surface protection, which shortens the production process and makes non-RE diffusion sources more competitive. The opportunity and future directions for non-RE GBD are also discussed in this review. Graphical abstract: Image, graphical abstract